Multiphysics analysis of a metal hydride moderated megawatt heat pipe reactor with burnable poisons - Feng, KuaiYuan; Hu, Jipu; Wang, Yihu; Cong, Tenglong; Gu, Hanyang; Guo, Hui (Frontiers in Energy Research, 2024)
With the development of nuclear energy, microreactors have received increasing interest among researchers in recent years. In this paper, a megawatt heat pipe reactor with metal hydride moderators and burnable poisons is proposed. The hydrogen stability of the reactor under accident conditions, including reactivity insertion accidents, loss of power conversion unit heat sink accidents, and heat pipe failure accidents are analyzed. In this work, Gd2O3 is introduced as a burnable poison in the form of mixing with the UO2 fuel. According to the results of the burnable poison design, the 0.1% mass fraction of Gd2O3 is selected as the burnable poison loaded in the core. Safety analysis indicates that the introduction of burnable poisons can be beneficial during the positive reactivity insertion accident as it can reduce the excessive reactivity at BOL, thus reducing power peak and preventing hydrogen dissociation in ZrH1.4 rods. However, during the loss of PCU heat sink accident, ZrH1.4 rods will dissociate regardless of the presence of burnable poisons, whereas YH1.7 rods show better hydrogen stability. Moreover, in the event of the heat pipe failure accident, ZrH1.4 rods are more susceptible to dissociation than YH1.7 rods. As a result, the YH1.7+BP core is a better choice compared with other designs proposed in this paper as it provides a relatively high temperature margin..